Adsorption recovery of phosphate from waste streams by Ca/Mg-biochar synthesis from marble waste, calcium-rich sepiolite and bagasse. (15th March 2021) - Deng, Wangde; Zhang, Dongqing; Zheng, Xiaoxian; Ye, Xingyao; Niu, Xiaojun; Lin, Zhang; Fu, Mingli; Zhou, Shaoqi
Abstract: In this study, marble waste and calcium-rich sepiolite were employed as Ca and Mg sources, and the agricultural waste was used as carbon source to synthesize two modified-biochar composites (Mar-BC800 and Sep-BC800) for removing phosphate from waste streams. The results show that Mar-BC800 and Sep-BC800 exhibited excellent performance for phosphate adsorption from aqueous solution in a wide pH range of 3–11, and the maximum adsorption capacity of phosphate by Mar-BC800 and Sep-BC800 was 263.17 and 128.21 mg/g, respectively. The adsorption process was best described by the pseudo second-order model and Langmuir model, and the dominating sorption mechanism for phosphate is that Ca 2+ or Mg 2+ with phosphate to form Ca5 (PO4 )3 OH, Mg3 (PO4 )2 and Mg3 (PO4 )2 ·4H2 O precipitate. Furthermore, Mar-BC800 and Sep-BC800 are simple to produce, the methods used to produce modified biochar are green, economic and environmentally-friendly, and the phosphate adsorbed modified biochar can applied as fertilizer to farmland soil, which have the functions of increasing soil fertility and improving soil physical and chemical properties. Graphical abstract: Image 1 Highlights: Ca/Mg-biochar was synthesized using marble waste, calcium-rich sepiolite and bagasse. Ca/Mg-biochar exhibited excellent phosphate adsorptive performance. The maximum adsorption capacities were 263.17 mg/g (Mar-BC800) and 128.21 mg/g (Sep-BC800). Surface precipitation was the main adsorption mechanism. The phosphate-adsorbed Ca/Mg-biochar can be used as fertilizer.